Design of a launch and control unit for anti-unmanned system on a boat - LI Erlei, ZHANG Fazhi (Zhihui kongzhi yu fangzhen)
The boat based on anti-unmanned system launch and control designed in this article integrates 70 mm unit, 40 mm unit and anti-armor unit. With the help of detection equipment, it can effectively deter and strike small and medium-sized UAVs, unmanned helicopters, suicide USVs, etc. in the airspace below 5 000 meters. The control unit adopts ARM+FPGA master-slave control structure, which fully plays the advantages of two different chips, and innovatively designs the hardware execution sequence of the launch process in the hardware circuit. While executing in strict accordance with the launch process sequence, it can ensure that no misfiring is caused by damage to any component, further ensuring the safety and reliability of the system.